Information Systems: its Security and Control - SRAVANI, AMUDA (IJRDO -Journal of Computer Science Engineering, 2018)
Data transformed to the Information and now the talk is of its Security. In the present world, the flow of information and its storage has begun an important task for every individual, organisation and also to the government. The security means protecting the information from an unauthorised access and use. The Information security is also concerned with the identification of an organization’s electronic information assets and the development. It is also concerned with that of the execution of tools and techniques, policies and procedures, standards and guidelines and so on, to ensure the confidentiality, integrity and availability of these assets.